Complex Study of Electronic States and Spectra of 3-Nitroformazans; Russian Physics Journal; Vol. 59, iss. 2 - Valiev R. R. Rashid Rinatovich; Drozdova A. K. Anna; Petunin P. V. Pavel Vasilievich; Postnikov P. S. Pavel Sergeevich; Trusova M. E. Marina Evgenievna; Cherepanov V. N. Viktor Nikolaevich (2016, 2016)
Title screen